PENERAPAN PROBLEM-BASED LEARNING DALAM PEMBELAJARAN STATISTIKA MAHASISWA MANAJEMEN PENDIDIKAN ISLAM - Wafirah, Milna (Institut Agama Islam Syubbanul Wathon Magelang, 2025)
This study aims to analyze the implementation of Problem-Based Learning (PBL) in improving the learning outcomes of students in the Statistics course within the Islamic Education Management program. The implementation of PBL focuses on collaborative problem-solving, which helps develop students' critical thinking, analytical skills, and problem-solving abilities. This research employs a quantitative approach with an experimental design involving two groups: the experimental group, which is taught using the PBL method, and the control group, which follows conventional learning methods. The students' learning outcomes are measured using pre-tests and post-tests, and the data are analyzed using paired t-test and independent t-test statistical tests. The results of the analysis indicate a significant improvement in learning outcomes after the application of PBL, with a significance level of 0.000, suggesting that PBL is better than conventional methods in enhancing students' understanding of statistical concepts. Additionally, the challenges faced in the implementation of PBL include time limitations, the readiness of lecturers, and some students' resistance to changes in the learning approach. This study recommends that PBL could serve as a better alternative for teaching statistics. However, it also emphasizes the need for increased preparation and training for lecturers to optimize its implementation and ensure its effectiveness in the learning process.